Health Literacy Orang Tua dan Self-Efficacy Anak dalam Pemilihan Makanan Sehat - Handayani, Nur Windi; Sibualamu, Khalida Ziah; Br Siragih, Dameria (Pustaka Galeri Mandiri, 2025)
A healthy diet plays an important role in supporting children’s optimal growth and development. Parents play a crucial role in shaping their children’s eating habits, which is closely related to their level of health literacy. In addition, children’s self-efficacy also influences their ability to independently choose healthy foods. The aim of this study was to analyze the relationship between parents’ health literacy and elementary school children’s self-efficacy in choosing healthy foods. This study employed a quantitative approach with a cross-sectional design, involving 50 parents and fifth-grade students at SDN 01 Pasar Manggis, South Jakarta. Parents’ health literacy was measured using the HLS-EU-Q16 questionnaire, which was adapted to focus on aspects related to children’s healthy eating patterns. Data were analyzed using the Spearman test. The results showed that the majority of parents (70%) had high health literacy, while most children (74%) had moderate self-efficacy. The Spearman test results indicated no significant relationship between parents’ health literacy regarding healthy eating and children’s self-efficacy in choosing healthy foods (p < 0.05). Therefore, additional approaches are needed, involving schools, the social environment, and active family engagement in shaping healthy eating behaviors among children.